P.019 Report from the Canadian Neurosurgery Research Collaborative – One year of resident-led multicentre research initiatives. (2nd June 2017) - Iorio-Morin, C; Kameda-Smith, M; Ahmed, SU; Bigder, M; Dakson, A; Elliott, C; Guha, D; Lavergne, P; Makarenko, S; Taccone, M; Tso, M; Wang, B; et al.
Abstract : Background: The Canadian Neurosurgery Research Collaborative (CNRC) was founded in November 2015 as a resident-led national network for multicentre research. We present an annual report of our activities.Methods: CNRC meetings and publications were reviewed and summarized. The status of ongoing and future studies was collected from project leaders.Results: In its first year, the CNRC produced two papers accepted for publication in the Canadian Journal of Neurological Sciences: A CNRC launch letter and a study of operative volume at Canadian neurosurgery residency programs. Three manuscripts are in preparation: 1) a study of the demographics of Canadian neurosurgery residents, 2) an assessment of mobile devices usage patterns and 3) a validation study of the most utilized neurosurgery mobile apps. In addition, protocols for two multi-centre studies are currently undergoing national Research Ethics Board review: A retrospective study of the incidence and predictors of cerebellar mutism and a prospective registry of external ventricular drain procedures and complications. The network is now a registered not-for-profit organization endorsed by the Canadian Neurosurgical Society.Conclusions: The CNRC is a feasibile, relevant and productive resident-led national research network. As the CNRC matures, we look forward to expanding the scope and impact of its projects.